An improved model and field calibration technique for measuring liquid water content in unfrozen and frozen soils with dielectric probes. Issue 5 (31st August 2022) - Amankwah, Seth K.; Ireson, Andrew M.; Brannen, Rosa
Abstract: Dielectric soil moisture probes can be used to obtain frequently logged field observations of volumetric water content, but because this is an indirect method, it is challenging to ensure that you have a suitable calibration relationship and parameters. Challenges are associated with (a) limitations in the probes' ability to accurately measure the soil bulk dielectric constant and (b) limitations in obtaining reliable direct observations to calibrate the probe against, due to the spatial heterogeneity in the field. Furthermore, in soils that freeze, we do not have a robust approach to account for the effect of ice on the instrument. In this study, we propose a calibration relationship for all dielectric probes that is physically based, parsimonious, accounts for errors in the bulk dielectric constant, and quantifies the uncertainty in the liquid water content caused by the presence of ice. We show that our relationship has a better performance and more realistic parameter values than existing approaches. To calibrate a dielectric probe in the field, we show that it is necessary to account for spatial heterogeneity in samples taken for calibration. There is value in taking simultaneous measurements of the bulk dielectric constant (using the same dielectric probe as is being calibrated) and gravimetric samples for water content at a number of points in space. Taking too few samples is likely to be misinformative—we show that it is better to not calibrate the probe at all than to calibrate it with too few data points. Core Ideas: Dielectric probes provide an indirect measure of liquid water content in unfrozen and frozen soils. The calibration relationship is hard to measure and there are limitations with existing models and parameter. We developed a modified calibration approach that fits the calibration data better.